Un sogno che affonda le radici nel mito: l’immortalità.Nota a RE JS (Disposal of Body) [2016] EWHC 2859 (FAM), [10] (Stato, Chiese e pluralismo confessionale, 2021)
SOMMARIO: 1. Introduzione - 2. La decisione dell’High Court of Family Division - 3. La crioconservazione: una nuova sfida per il diritto? - 4. Aspetti bioetici della crionica - 5. La soluzione si trova dove il sogno trova la propria origine: conclusioni.A Dream rooted in Myth: Immortality. Note a RE JS (Disposal of Body) [2016] EWHC 2859 (FAM), [10]ABSTRACT: This paper addresses the problem of cryonics through the analysis of a pronunciation of the High Court of Family Division. A first part is dedicated to the examination of the decision taken and then proceed to the analysis of the bioethical and biolaw issues that cryopreservation and neuropreservation pose. The aim is to introduce the biolaw debate in relation to the emergence of this new practice by highlighting the criticality of the same, such as, for example, that of not having adequate scientific basis. Given that the pursuit of immortality has its roots in Greek mythology, a possible solution could be to recall the warning that the same mythological narratives handed down.